2004
DOI: 10.1097/00001756-200405190-00023
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral hemodynamics and processing speed during category learning

Abstract: The Wisconsin Card Sorting Test (WCST) is a commonly used paradigm of category learning with two alternating and distinct processes, maintaining set and set shifting that have been characterized by functional transcranial Doppler sonography (fTCD) of the basal cerebral arteries. Further, repeated WCST administrations resulted in improved speed of solution. This study addressed the question of whether optimised speed during maintaining set or set shifting is associated with changes of cerebral hemodynamics as m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
2
0
3
Order By: Relevance
“…Such a relationship may only appear with greater degree of hypoxia: even at 78% SpO 2 only subtle cognitive deficit is found (Noble, Jones & Davies, 1993). Faster performance on cognitive tests is associated with higher mean CBFV in anterior cerebral vessels in sea‐level adults (Schuepbach, Bader, Hell & Baumgartner, 2004; Duschek, Schuepbck & Schandry, 2008). However, in the present study no correlation between psychomotor speed and CBFV was found.…”
Section: Discussionmentioning
confidence: 99%
“…Such a relationship may only appear with greater degree of hypoxia: even at 78% SpO 2 only subtle cognitive deficit is found (Noble, Jones & Davies, 1993). Faster performance on cognitive tests is associated with higher mean CBFV in anterior cerebral vessels in sea‐level adults (Schuepbach, Bader, Hell & Baumgartner, 2004; Duschek, Schuepbck & Schandry, 2008). However, in the present study no correlation between psychomotor speed and CBFV was found.…”
Section: Discussionmentioning
confidence: 99%
“…Functional transcranial Doppler sonography (fTCD) has been shown to detect specific alterations in MFV during the WCST [ 10 , 12 , 13 ], the Tower of Hanoi (TOH) [ 12 ] and the SOC [ 11 ]. In a study in patients with schizophrenia, preliminary results suggested reduced MFV in the area of the MCA during performance of the TOH [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Так, D. Schuepbach и соавт. [36] при оценке эффектов устойчиво-сти и потери стратегии выполнения задания и изменения СК в СМА в обоих полушариях обнаруживали пик (макси-мум) в передних зонах, что свидетельствует о большей во-влеченности передних отделов.…”
Section: о б з о р ыunclassified